Afrotropical weevils of the Cadoderus Marshall generic complex (Coleoptera: Curculionidae: Entiminae: Embrithini). Part 1. Genera: Cadoderus Marshall, 1926; Sphrigodellus Marshall, 1942 and Oncophyes Marshall, 1942 - Yunakov, Nikolai (Zootaxa, 2012)
The canopy dwelling weevils of the genus Cadoderus and allied genera demonstrate significant diversity in fragmentedmontane and gallery forests of East Africa. Adults have various cryptic coloration or vestiture to hide them among branch-es covered with lichens and moss. Cadoderus Marshall, 1926, Sphrigodellus Marshall, 1942, and Oncophyes Marshall,1942 are reviewed and redescribed. Eighteen new species are described: Cadoderus weisei sp. n. (Tanzania: West Usam-bara Mts.), C. burundi sp. n. (Burundi: Ruvube N.P.), C. grebennikovi sp. n. (Tanzania: Nguru Mts.), C. olivaceus sp. n.(Tanzania: Nguru Mts.), Sphrigodellus minutus sp. n., S. gusarovi sp. n., S. nasutus sp. n., S. parecola sp. n., S. viridegr-iseus sp. n., S. kiverengei sp. n. (Tanzania: Pare Mts.), S. usambaricus sp. n., S. kwamkoroensis sp. n. (Tanzania: EastUsambara Mts.), S. nguruensis sp. n. (Tanzania: Nguru Mts.), S. lineatus sp. n. (Tanzania: Udzungwa Mts.), S. sundi sp.n. (Tanzania: Mt. Kilimanjaro), S. aberdarecola sp. n. (Kenya: Aberdare Mountain Range), S. taitae sp. n. (Kenya: TaitaHills), Oncophyes cadoderoides sp. n. (Tanzania: Usambara Mts.). Genitalia of both sexes of all known taxa are exten-sively studied and illustrated for the first time. A modified key to genera and species of the Cadoderus-complex is given.Lectotypes are designated for Ellimenistes bellus Faust, 1896, E. mysticus Faust, 1900, E. amoenus Hartmann, 1904, Barianus centralis Hustache, 1929 and Cadoderus lepidus Marshall, 1940.